Hubungan Gaya Belajar dan Dukungan Orangtua dengan Minat Belajar pada Remaja di Gereja HKBP Distrik XXXI Medan Utara - Krisman Krisman; Hasanuddin Hasanuddin; Suaidah Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to determine the relationship between learning style and parental support with interest in learning in adolescents. Using quantitative methods with a survey approach. A sample of 169 people from 312 populations with simple random sampling technique. Based on the results of the study, it is known that there is a positive and significant relationship between learning styles and interest in learning seen from the coefficient value (R2) = 0.039 with p = 0.010 <0.050. Furthermore, there is a positive and significant relationship between parental support and interest in learning seen from the coefficient value (R2) = 0.087 with p = <0.001 <0.050, then it is known that there is a positive and significant relationship between learning styles and parental support with learning interest seen from the value of the coefficient (R2) = 0.100 with p = <0.001 <0.050.